The conviction of self-efficacy and midwives’ education - Krysa, Justyna; Iwanowicz-Palus, Grażyna Jolanta; Korżyńska-Piętas, Magdalena; Kicia, Mariola; Szlendak, Beata (Journal of Education, Health and Sport, 2018)
Abstract The interest in scientific research of the self-efficacy phenomenon provides new data and reveals further relationships between this phenomenon and the functioning of the individual in the society. The Albert Bandura’s socio-cognitive theory presents its important and the most popular theoretical construct - self-efficacy, which is a part of the cognitive components of personality. It is an assessment of the individual's competences, its conviction about the possibility of managing planned activities in a given field. Studies on the relationship between coping with the learning process and self-efficacy seem to be particularly interesting. In the analysis of the problem, there are a number of personality variables that could be important for undertaking and continuing education and training in adulthood, which is particularly important among people performing medical professions, including midwives. Motivation, conscientiousness, conviction about self-efficacy or cognitive abilities are mentioned in literature of the subject.